PERANAN LEMBAGA PEMBINAAN KHUSUS ANAK KELAS I PALEMBANG DALAM PELAKSANAAN PENDIDIKAN DAN PELATIHAN TERHADAP NARAPIDANA ANAK (Faculty of Law, University of Palembang, 2022)
Children who are in conflict with the law and are under the supervision of Correctional Institutions are now in dire need of proper protection and services while in development because they are still under psychological influence and pressure that is less favorable for the future. Correctional officers play a role in carrying out care and guidance for inmates and students, both suspects, defendants and prisoners in accordance with statutory regulations. In the implementation of coaching, education and training for the Officers of the Palembang Class I Children's Special Guidance Institute, it is still not fully implemented in accordance with the mandate due to constraints on facilities and infrastructure. There is a need for criminal alternatives for children who have committed criminal acts to avoid the negative impact of the implementation of imprisonment. It is also hoped that there will be an increase in cooperation with related social agencies, one of which is the local Education Office in providing non-formal education so that the education of the children assisted by the children does not stop.